Caesarean section rates across Europe and its impact on specialist training in Obstetrics: A qualitative review by the Standing Committee of Hospital Visiting Programme for Training Recognition of the European Board and College of the Obstetrics and Gynaecology (EBCOG) - Wladimiroff, Juriy; Tsiapakidou, Sofia; Mahmood, Tahir; Velebil, Petr (European journal of obstetrics, gynecology, and reproductive biology, 2025)
Information is presented from hospital visiting reports with focus on Caesarean section and vaginal instrumental delivery rates from training units in European countries during the period 1999-2023. In a considerable number of countries training units were audited more than once, allowing assessment of trends in both obstetric interventions. There is a notable rise in Caesarean section rate in a number of European countries, with the highest rates in Poland (55.1%), Turkey (54.8%) and Greece (48.6%). Conversely Caesarean sections were low in France (19.3%) associated with a higher rate of instrumental vaginal delivery rates. Some countries like Germany and Poland have high variability in their rates, indicating fluctuations or regional differences over the years. Vaginal instrumental delivery rates varied across countries having very low rates (Turkey with 1.0% and Poland with 1.2%) and others having relatively high rates (like Switzerland, France and Belgium). Germany and Belgium showed a balanced use of both Caesarean sections and vaginal instrumental deliveries but with considerable variability in both practices. Countries in Central Europe display marked differences in Caesarean section rate: Hungary 37.8%; Slovakia 34.5%, Czech Republic 27.5% and Slovenia 20.7%. Apart from Poland (1.2%), differences in vaginal instrumental delivery rate between these countries are relatively small with Hungary 2.7%, Slovakia 2.8%, Czech Republic 2.9% and Slovenia 2.9%. Low instrumental delivery rates have major effect on the quality of training for the trainees in their formative years. Having a limited experience in this area of clinical practice would influence their future clinical obstetric practice.
Keywords: European hospitals; gynekologie; Female; Europe; EBCOG Hospital Visiting Programme; ženské pohlaví; Caesarean section trends; Training; lidé; Evropa; těhotenství; Obstetrics; Obstetrics trainees; Accreditation; Gynecology; porodnictví; Cesarean Section; Pregnancy; Vaginal instrumental delivery; císařský řez; Humans